2020
DOI: 10.1007/s00125-020-05126-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes through a 3D lens: organoid models

Abstract: Diabetes is one of the most challenging health concerns facing society. Available drugs treat the symptoms but there is no cure. This presents an urgent need to better understand human diabetes in order to develop improved treatments or target remission. New disease models need to be developed that more accurately describe the pathology of diabetes. Organoid technology provides an opportunity to fill this knowledge gap. Organoids are 3D structures, established from pluripotent stem cells or adult stem/progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 104 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…In our study, we evaluated the effect of chronic hyperglycemia on intestinal cell differentiation using small intestinal organoid platforms that analyzed the involvement of metabolic perturbations in EEC physiology, providing a theoretical basis to the study of diabetes physiopathology. Recent studies have shown that organoids represent a platform to explore the differentiation of intestinal cells and to test the capacity of novel molecules to manipulate the density of EECs for treating metabolic disease [18][19][20]. To date, how diabetes or other metabolic diseases could impair intestinal cell differentiation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we evaluated the effect of chronic hyperglycemia on intestinal cell differentiation using small intestinal organoid platforms that analyzed the involvement of metabolic perturbations in EEC physiology, providing a theoretical basis to the study of diabetes physiopathology. Recent studies have shown that organoids represent a platform to explore the differentiation of intestinal cells and to test the capacity of novel molecules to manipulate the density of EECs for treating metabolic disease [18][19][20]. To date, how diabetes or other metabolic diseases could impair intestinal cell differentiation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a snapshot of the chronic hyperlipidemia effect on intestinal cell differentiation by using small intestinal organoid platforms. Organoids allow for the investigation of how biologically active intestinal cells interact in the gut, how TFs regulating gut cell differentiation interact with each other, and how nutritional changes causing metabolic diseases could impair these aspects [ 16 , 28 , 29 ]. In addition, our 3D platform could represent a starting point for the development of on-chip model in order to obtain an enhancement of the understanding of physiopathological alterations that could lead to an improvement in the prevention and treatment of complex chronic diseases such as obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A human microfluidic organ-chip platform was developed to study the connection among thymic epithelia, hematopoietic stem cells, islet β cells in T1D and pancreatic islet-liver cross-talking in type 2 diabetes (T2D) 140 . Therefore, inter-organ communication in diabetes would be modelled by human microfluidic organ-chip platform 141 , 142 . Moreover, islet organoids with microfluidic systems could also be a simple, advanced method for high-throughput drug screening, which was proven in 2019 143 , 144 .…”
Section: Approach For Producing Human Islet-like Organoidmentioning
confidence: 99%